PENGARUH PRODUK DOMESTIK BRUTO (PDB), INFLASI DAN TINGKAT PENGANGGURAN TERHADAP PROFITABILITAS PERBANKAN - Deandra Afifah Zerlinda Maidin; Evan Seprianto; Indah Permatasari (Jurnal MANAJERIAL, 2022)
Banking as a provider of monetary activities is a crucial part of the economy of rustic. The most common concept of banking is as an establishment that receives funds from the general public to be channeled to parties who need funds or capital. Therefore, the performance of the banking sector is a crucial aspect when assessing economic development in a country. The population used in this study was all 33 banks listed on the Indonesia stock exchange during the 2014-2018 period. This study used the entire population of 33 banks as the sample because it was felt that the population was too small to sample. The findings revealed that the variables Gross Domestic Product (GDP), Inflation, and Unemployment all had a negative effect on Return On Equity (ROE) at the same time.